2009
DOI: 10.1590/s0074-02762009000400021
|View full text |Cite
|
Sign up to set email alerts
|

The circulation of human astrovirus genotypes in the Central West Region of Brazil

Abstract: Out of 1,588 faecal samples of children taken from three locations of the Central West Region of Brazil, 57 were positive for astroviruses (HAstVs) using reverse transcription-polymerase chain reaction (RT-PCR). They were genotyped by nested , , , and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…Three HAstVs genotypes co-circulated in Belém during the six months of study with HAstV-1 as the most prevalent 6,16,39,45 genotype (82.2%), as reported elsewhere . The concurrent circulation of other genotypes was observed in 6,10,36,39 various settings in Brazil as well as across the globe .…”
Section: Fromsupporting
confidence: 77%
See 1 more Smart Citation
“…Three HAstVs genotypes co-circulated in Belém during the six months of study with HAstV-1 as the most prevalent 6,16,39,45 genotype (82.2%), as reported elsewhere . The concurrent circulation of other genotypes was observed in 6,10,36,39 various settings in Brazil as well as across the globe .…”
Section: Fromsupporting
confidence: 77%
“…The concurrent circulation of other genotypes was observed in 6,10,36,39 various settings in Brazil as well as across the globe . similar results were observed in Rio de Janeiro .…”
Section: Frommentioning
confidence: 95%
“…For example, RVAs have been predominantly detected among children up to 24 months of age (Camarota et al 1992, Cardoso et al 2003, Costa et al 2004, with a similar age range observed for astroviruses (Silva et al 2009) and adenoviruses (Cardoso et al 1989). The caliciviruses were detected in children up to 36 months of age (or 36 months-old) (Borges et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, in the Central-West Region of Brazil, many studies have focused on the investigation of other gastroenteric agents in this population (Cardoso et al 1989, 2003, Camarota et al 1992, Borges et al 2006, Oh et al 2006, Andreasi et al 2008, Silva et al 2009). Therefore, the objective of this study, the first conducted in this region, was the detection of HBoV-1 and HBoV-3 in faecal samples obtained from children under five years of age presenting with acute gastroenteritis.…”
mentioning
confidence: 99%
“…Data from the literature show that the detection rates for these viruses among children with gastroenteritis in Brazil vary between 12 and 47% 4,14,[19][20][21] . However, there is no information available on the prevalence of these agents among the adult female population in Brazil.…”
Section: Resultsmentioning
confidence: 99%